Incidence of melanoma in organ transplant recipients in Alberta, Canada. Issue 10 (23rd September 2016) - Tran, Mimi; Sander, Megan; Ravani, Pietro; Mydlarski, P. Régine
Abstract: Background: Many studies have documented the increased risk of non‐melanoma skin cancers in organ transplant recipients (OTRs). However, the incidence of melanoma is less well defined. To date, there have been no studies on the incidence of melanoma in Canadian OTRs. Herein, we determine the incidence and clinical features of melanoma in a cohort of OTRs in Southern Alberta, Canada. Methods: We used the Southern Alberta Transplant database to identify kidney and liver transplant recipients between the years 2000 and 2012. This population was cross‐referenced with the Alberta Cancer Registry for a diagnosis of melanoma. The clinical features of all cases were obtained, and the standardized incidence rate was calculated. Results: We identified 993 OTR patients, representing 5955 person‐years. Only one patient developed a melanoma post‐transplant, and this was a nodular melanoma. The age‐standardized incidence rate was 11 per 100 000 (0.6 per 5955), compared to 13.4 per 100 000 in the general Alberta population (incidence rate ratio of 1.29, with 95% confidence interval of 0.17 to 9.82). Conclusions: This is the first Canadian study to investigate the association between organ transplantation and melanoma. Our study did not identify an increased risk of developing a de novo melanoma post‐transplant.